Features of the Old English medical practice on the example of the herbalist Leechbook III - A. A. Moiseeva (Российский журнал истории Церкви)
Old English medicine, reflected in the totality of medical texts compiled in Anglo-Saxon, serves as a unique synthesis of early medieval cultural and religious ideas. The herbalist Leechbook III is one of the most representative sources on the history of Old English medicine. The analysis of the text allows us to highlight the principles that formed the basis of medical practice in Anglo-Saxon England. Through the prism of this medical essay, the researcher also gets the opportunity to look at the features of the religious worldview of the Anglo-Saxons.